2012
DOI: 10.1177/0363546512449424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Identification of Rotator Cuff Retears After Repair

Abstract: The results of this study indicate that there is substantial variability when evaluating MRI scans after rotator cuff repair. Intact rotator cuff repairs or full-thickness retears can be identified with moderate reliability. These findings indicate that additional imaging modalities may be needed for accurate assessment of the repaired rotator cuff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 39 publications
(23 reference statements)
2
77
0
1
Order By: Relevance
“…First, because both sides of the infraspinatus tendon are covered by the patellar tendon, this telescoping structure guarantees contact between the 2 tendon tissues, provided that the relative displacement does not exceed the length of patellar tendon (Figure 5). This setup may be able to diminish potential gap formation in the healing process from infraspinatus tendon retraction, which contributes to postoperative failure with current repair methods 29; 30 . Second, the higher stiffness at the TFBC–greater tuberosity repair site (i.e., the shorter displacement compared with the traditional repair) provides a more secure environment for tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…First, because both sides of the infraspinatus tendon are covered by the patellar tendon, this telescoping structure guarantees contact between the 2 tendon tissues, provided that the relative displacement does not exceed the length of patellar tendon (Figure 5). This setup may be able to diminish potential gap formation in the healing process from infraspinatus tendon retraction, which contributes to postoperative failure with current repair methods 29; 30 . Second, the higher stiffness at the TFBC–greater tuberosity repair site (i.e., the shorter displacement compared with the traditional repair) provides a more secure environment for tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that, in the preoperative setting, MRI (sensitivity, 92.1%, and specificity, 92.9%) and ultrasound (sensitivity, 92.3%, and specificity, 94.4%) are relatively equivalent, with MR arthrogram (sensitivity, 95.4%, and specificity, 98.9%) demonstrating better sensitivity and specificity at detecting full-thickness rotator cuff tears 51 . Khazzam et al 52 examined interobserver and intraobserver reliability of MRI following rotator cuff repair and found only moderate agreement. In a recent study, Park et al 53 demonstrated that ultrasound showed excellent reliability following rotator cuff repair.…”
Section: Clinical Outcome Scoresmentioning
confidence: 99%
“…One image cannot fully capture morphological changes in other areas of the muscle, 14 but little work has focused on the acquisition of three-dimensional measurements of muscle morphology to evaluate whether a single image is indicative of three-dimensional muscle information. Further, the Goutallier score does not have high reliability, 1518 suggesting that more objective methods should be used. 15,16 …”
Section: Introductionmentioning
confidence: 99%